The comparative analysis of lithuanian and Latvian transit transport - Palšaitis, Ramūnas; Bazaras, Darius; Labanauskas, Gintautas (Transport, 2004)
The results of the comparative analysis of Lithuanian and Latvian transit transport show that transit transport systems of these countries compete against each other. Latvia has evidently better developed harbours, which are able to process bigger scopes of loads. In comparison with Lithuanian transit transport system, Latvia has the competitive advantages, which are determined by its historical and trading relations, infrastructure, socio‐cultural environment and traditions as well as more favourable integration with other systems of transport. In this article general indicators of sea and railroads transit transport as well as the problems, which impede the development of transport system, are analysed. It is suggested to pay attention to the proposed strategic directions of transit services development as well as to solve (on the governmental level) the questions of competition choosing the cooperation policy of Lithuanian and Latvian systems of transit transport. First Published Online: 27 Oct 2010